A study on passengers' alighting and boarding process at metro platform by computer simulation. (February 2020) - Li, Zitong; Lo, S.M.; Ma, Jian; Luo, X.W.
Highlights: Passenger's non-compliance behavior is defined and observed. Critical time indicators are defined to measure the alighting and boarding efficiency. A simulation model is proposed to simulate passengers' alighting and boarding process at metro platform. Effects of Passenger's non-compliance behaviors under different passenger volume conditions are analyzed. Different alighting and boarding rules could be applied to increase alighting and boarding efficiency. Abstract: Passengers' alighting and boarding process in metro stations has attracted increasing research attention since it has significant influence on the platform passenger distribution as well as the train dwell time. In this study, a field survey was firstly performed in a densely populated metro station at downtown area in Hong Kong to observe passengers' alighting and boarding characteristics and collect sample data. One commonly existing phenomenon is found that boarding passengers start to get aboard even when there are alighting passengers still inside the metro carriage. This is defined as passengers' non-compliance behaviors in this paper. In addition, time indicators are defined to measure the alighting and boarding efficiency. Then a microscopic pedestrian simulation model based on the Social Force Model is proposed to simulate the passengers' alighting and boarding patterns at metro platform. The verification result shows the good applicability of the proposed model to simulate the actual situation. Finally, several simulation tests are conducted to explore the impacts that passengers' non-compliance behaviors have on the alighting and boarding efficiency in different passenger volume conditions. The simulation result shows that higher level of passengers' non-compliance behaviors leads to longer passenger's alighting duration and boarding duration, but the influence on the overall transaction time is related to different passenger volume conditions. Thus, metro station facility could apply different alighting and boarding rules in different passenger volume conditions to increase alighting and boarding efficiency.